2001
DOI: 10.1002/jcp.10038
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor modulates the expression of glycophorin A and c‐kit and inhibits erythroid differentiation in K562 cells

Abstract: Basic fibroblast growth factor (bFGF) is produced by bone marrow stromal cells as well as by normal and leukemic hematopoietic cells. In this study, we examine the direct effects of bFGF on erythroid differentiation in K562 cells in order to determine whether bFGF can promote the expression of a primitive phenotype. Low levels of bFGF inhibited erythroid differentiation as evidenced by decreased expression of glycophorin A and increased expression of c-kit. bFGF also increased both the numbers and the sizes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…tissues, and respond to FGF-2 (Cross and Claesson-Welsh, 2001;Burger et al, 2002). However, the role of FGF-2/FGFR-1 in vascular development remains controversial and it has not been clarified through genetic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…tissues, and respond to FGF-2 (Cross and Claesson-Welsh, 2001;Burger et al, 2002). However, the role of FGF-2/FGFR-1 in vascular development remains controversial and it has not been clarified through genetic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of TGF-β to a rat prostate basal cell line in the absence of mitogens induces differentiation while the presence of mitogens, such as IGF-1, suppresses TGF-β-induced differentiation, promoting a more primitive basal phenotype (40). Similarly Narine et al (41) demonstrated that either EGF or FGF-2 ablated TGF-β-induced growth inhibition of fibroblast proliferation and FGF-2 inhibited differentiation, as evidenced by loss of alpha smooth muscle actin expression, while Burger et al (42) demonstrated that FGF-2 maintains erythroid cells in a primitive state while TGF-β promotes their differentiation. SCF and its receptor, c-Kit, have been implicated as regulators of cellular proliferation and differentiation of progenitor cells in a variety of systems, including hematopoiesis, gametogenesis and melanogenesis (26,43,44).…”
Section: Discussionmentioning
confidence: 97%
“…Purif 13:135-146, 1995 6. Pfeilschifter J, Mundy GR, Roodman GD: Interleukin 1 and by bone marrow stromal cells [46]. After bone resorption tumor necrosis factor stimulate the formation of human osteoclastprocesses, latent factors, including bFGF, stimulate the like cells in vitro.…”
Section: Of Hpt Preoperatively Bone Marrow Fibrosis Regressedmentioning
confidence: 99%